THE SIMULATION OF A FABRY-PEROT INTERFEROMETER - Gi-Hyuk Choi; David Rees (Journal of Astronomy and Space Sciences, 1997)
A Fabry-Perot interferometer has a very high (~1,000,000) resolution, so recently this has been widely used for many fields of space science. To understand the working principle of this a mathematical modeling is needed, and to analyze the interferogram it is essential to know the precise instrument function. The spectrum from the interferometer is mixed with a true signal from the light source and the instrument function through convolution. The true signal has the information about the quantum state of mo lecules, temperature and bulk motion of the gas. Therefore if we model the signal and convolve this with the theoretical instrument function we can predict the spectrum for the real case.